How well do we care for patients with end stage chronic obstructive pulmonary disease (COPD)? A comparison of palliative care and quality of life in COPD and lung cancer. Issue 12 (1st December 2000) - Gore, J M; Brophy, C J; Greenstone, M A
Abstract : BACKGROUND: Patients with severe chronic obstructive pulmonary disease (COPD) have a poor quality of life and limited life expectancy. This study examined whether these patients were relatively disadvantaged in terms of medical and social care compared with a group with inoperable lung cancer. METHODS: An open two group comparison was made of 50 patients with severe COPD (forced expiratory volume in one second (FEV1 ) <0.75 l and at least one admission for hypercapnic respiratory failure) and 50 patients with unresectable non-small cell lung cancer (NSCLC). A multi-method design was used involving standardised quality of life tools, semi-structured interviews, and review of documentation. RESULTS: The patients with COPD had significantly worse activities of daily living and physical, social, and emotional functioning than the patients with NSCLC (p<0.05). The Hospital Anxiety and Depression Scale (HADS) scores suggested that 90% of patients with COPD suffered clinically relevant anxiety or depression compared with 52% of patients with NSCLC. Patients were generally satisfied with the medical care received, but only 4% in each group were formally assessed or treated for mental health problems. With regard to social support, the main difference between the groups was that, while 30% of patients with NSCLC received help from specialist palliative care services, none of the patients with COPD had access to a similar system of specialist care. Finally, patients in both groups reported a lack of information from professionals regarding diagnosis, prognosis and social support, although patients' information needs were disparate and often conflicting. CONCLUSION: This study suggests that patients with end stage COPD have significantly impaired quality of life and emotional well being which may not be as well met as those of patients with lung cancer, nor do they receive holistic care appropriate to their needs.